LOMBA CERITA BERSERI : LOMBA CERITA BERSERI - Brantasari, Mahkamah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Widya Gama Mahakam Samarinda, 2021)
Storytelling is an activity that has always been carried out by our society from generation to generation. Storytelling has many benefits including conveying activities that have been carried out, conveying ideas, advice, experiences, from one person to another. Storytelling is able to develop listening and language skills, increase vocabulary and increase speaking skills. Able to develop children's thinking power because children focus and imagine stories and can develop symbolic abilities, develop children's social emotional nature towards their environment, are trained to receive and store information, have creative potential and are able to absorb the moral messages conveyed. In order for stories to be more interesting, they usually use image media in their implementation, so that storytelling starts from the first image to the end, the story is expected to be interesting and more meaningful for children. In order for the ability to develop children's creative potential through the diversity of story ideas told, a series of story competitions is held with the theme of increasing the creativity of teachers, early childhood students and also the general public.